Long-Term Inhalation of Ultrafine Zinc Particles Deteriorated Cardiac and Cardiovascular Functions in Rats of Myocardial Infarction - Huo, Yunlong; Li, Li (Frontiers in Physiology, 2022)
Substantial ultrafine zinc particles exist in air pollutions. The level of Zn concentrations in serum and tissue could affect patients with myocardial infarction (MI). The aim of the study is to investigate the change of cardiac functions and peripheral hemodynamics in MI rats after long-term inhalation of ultrafine Zn particles. Coronary artery ligation surgery was performed to induce MI in Wistar rats. The inhalation of ultrafine Zn particles was carried out for 6 weeks after the operation. Physiological and hemodynamic measurements and computational biomechanics analysis were demonstrated in eight groups of rats at postoperative 4 and 6 weeks. There was no statistical significance between shams and shams with inhalation of ultrafine Zn particles. There were significant impairments of cardiac and hemodynamic functions in MI rats. In comparison with MI rats, the inhalation of ultrafine Zn particles for 4 weeks slowed down the progression from MI to heart failure, but the inhalation for 6 weeks accelerated the process. The long-term inhalation of ultrafine zinc particles induced excessive accumulation of zinc in serum and tissue, which deteriorated cardiac and hemodynamic dysfunctions in MI rats.